Microzooplankton grazing upon picoplankton : the effect of future carbon dioxide levels in the ocean - García Neefjes, Kai (2016)
Impacts of ocean acidification on marine biota were observed in a wide range of marine systems. However, there is no abundant literature about the effect of a future high pCO2 scenario on microzooplankton grazing in the ocean. Here, we used two different mesocosms under the Bioacid/Kosmos Project (GEOMAR) to study the response of high pCO2 concentrations upon phytoplankton growth and microzooplankton grazing. Mesoscosms were installed inside the Taliarte harbor (east coast of Gran Canaria), and two pCO2 levels were assayed, one simulating present conditions (400 µatm) and another at future scenarios of increased pCO2 (1450 µatm). Microzooplankton grazing experiments were developed using the 2-point method, which is a modification of the classical dilution method. Our results did not show the high pCO2 treatment affecting directly the picoplankton communities (picoeukaryote and Synechococcus organisms), but we found some significant correlations between grazing and growth rates in both treatments.